Palliative Care for People Living With Heart Disease—Does Sex Make a Difference? - Sobanski, Piotr Z.; Krajnik, Malgorzata; Goodlin, Sarah J. (Frontiers in Cardiovascular Medicine, 2021)
The distribution of individual heart disease differs among women and men and, parallel to this, among particular age groups. Women are usually affected by cardiovascular disease at an older age than men, and as the prevalence of comorbidities (like diabetes or chronic pain syndromes) grows with age, women suffer from a higher number of symptoms (such as pain and breathlessness) than men. Women live longer, and after a husband or partner's death, they suffer from a stronger sense of loneliness, are more dependent on institutionalized care and have more unaddressed needs than men. Heart failure (HF) is a common end-stage pathway of many cardiovascular diseases and causes substantial symptom burden and suffering despite optimal cardiologic treatment. Modern, personalized medicine makes every effort, including close cooperation between disciplines, to alleviate them as efficiently as possible. Palliative Care (PC) interventions include symptom management, psychosocial and spiritual support. In complex situations they are provided by a specialized multiprofessional team, but usually the application of PC principles by the healthcare team responsible for the person is sufficient. PC should be involved in usual care to improve the quality of life of patients and their relatives as soon as appropriate needs emerge. Even at less advanced stages of disease, PC is an additional layer of support added to disease modifying management, not only at the end-of-life. The relatively scarce data suggest sex-specific differences in symptom pathophysiology, distribution and the requisite management needed for their successful alleviation. This paper summarizes the sex-related differences in PC needs and in the wide range of interventions (from medical treatment to spiritual support) that can be considered to optimally address them.